NAIB OF IMAMAT AND ADVISOR OF SHAMIL HAJI YUSUF: BIOGRAPHY IN THE CONTEXT OF CRITICISM OF AUTOBIOGRAPHY - Musaev, Mahac Abdulaevic (History, Archeology and Ethnography of the Caucasus, 2021)
A Turkish citizen of Chechen origin, Haji Yusuf played a significant role in the formation of the administrative and military institutions of the Imamat, the construction of fortifications, in communications with officials of the Ottoman Empire; he is considered one of the important figures of the Shamil era, "the behind-the-scenes mind of the imam."Several studies of different times have been devoted to the fate of Haji Yusuf, but quite a lot of time has passed since their publication, new information has been revealed that make it possible to clarify the details of his life path and describe in more detail the biography of this remarkable personality. His scientific biography helps to raise the level of knowledge of the life of a particular person, to recreate the history of a person in connection with historical realities and social reality, to characterize time against the background of a person.For this, his autobiographical information was used, as well as an array of identified sources and materials, the analysis of which was made in comparison. The results obtained demonstrate the stages of the life of Haji Yusuf in chronological order: birth in the village. Aldy; the family moved to the Ottoman Empire, received an education there and then served in the army of the Egyptian Pasha (until 1834); return to the Caucasus, work as a home teacher for the Kabardian prince (1834 - 1839); desire to return to Turkey and departure to the Black Sea coast of Circassia (1839 - 1841); establishing contacts and moving to Imam Shamil (1841); activity in the service of the Imamat - naib, adviser, engineer (until 1854); exile for attempting to discredit the imam (1854 - 1856); flight to the Russians (1856). In addition, the study publishes the legacy of Haji Yusuf - maps and diagrams drawn by him to inform the officials of the Ottoman Empire about the Imamate.